Polylactic acid and lanolin based nanofibrous structures for wound management application - UZUN, MUHAMMET (My University, 2022)
Polylactic acid (PLA) polymer and wool oil (lanolin) have been used to develop nanostructures for wound dressing management. Lanolin has been extracted from raw wool surfaces and used as a by-product in wide range of pharmaceutical areas. Different solutions with varying concentration of the PLA/lanolin and sodium alginate/lanolin solutions have been prepared and then nanostructures are developed using electrospinning method. The developed structures are aimed to use as smart wound dressings. During the production stage, the parameters of the electrospinning process have been changed to develop the optimum structures. The effect of solution concentrations on the applied voltage and the distance between the pipette tip and the collector is highlighted. The spinnability of lanolin is the main objectives of this study and the PLA/lanolin nanostructures are designed and manufactured successfully. The essential test methods have been performed to measure the usability of the produced materials as wound dressings. These are liquid absorption capacity, horizontal/vertical wicking, SEM, degradation, pH, antibacterial assay, and tensile properties. From the tested parameters, it is obviously found that the use of PLA/lanolin as wound dressing is suitable according to initial in vitro test results.
Keywords: Tekstil Mühendisliği ve Teknolojisi; Mühendislik ve Teknoloji; Textile Engineering and Technology; Engineering and Technology; MALZEME BİLİMİ, TEKSTİL; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MATERIALS SCIENCE, TEXTILES; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); General Materials Science; Physical Sciences